The Contribution Of The Dompet Dhuafa Waspada Amil Zakat Institution To The Education Of Orphans And The Under-Privileged In Medan City - Alaska, Yogi; Panggabean, Hadi Saputra (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
Education is the basic right of every child, including orphans and the poor. In the Indonesian context, education not only functions as a means of transferring knowledge, but also as a tool to improve the quality of life (Rahman et al., 2022) and shape the character of the nation's next generation. However, the reality on the ground shows that there are many orphans and poor people who Mas Dompet Dhuafa Waspada as one of the Amil Zakat institutions in North Sumatra has an important role in providing educational assistance for orphans and poor people. Through the various programs it runs, this institution seeks to answer the educational challenges faced by this group. However, along with the increasing need for education and the complexity of existing social problems, the effectiveness of the programs implemented by these institutions needs to be critically evaluated. They face various challenges in getting a decent education. This research aims to analyze the implementation of the education program run by Dompet Dhuafa Waspada and its impact on the education of orphans and poor people in Medan City. By using a qualitative approach, this research is expected to provide in-depth insight into program implementation and the challenges faced by institutions in meeting the educational needs of children who are able to receive it.